Longitudinal prospective anthropometric evaluation in Caucasian prepubertal children with lactose intolerance - Mauro Lizzi; Laura Sgrazzutti; Annamaria Porreca; Paola Di Filippo; Chiara Cauzzo; Sabrina Di Pillo; Francesco Chiarelli; Marina Attanasi (Frontiers Media S.A., 2023)
IntroductionThe health consequences of lactose intolerance remain unclear. We studied the association of lactose intolerance with growth in children.MethodsIn this prospective case-control study, we compared Caucasian prepubertal children with lactose intolerance (LI) [n = 30, median age = 7.87 years (3.00-12.75)] to healthy controls [(n = 75, median age = 2.25 years (2.00-7.25)]. A lactose tolerance test was performed for lactose intolerance diagnosis. The gastrointestinal symptom score was administered at baseline and after a lactose-free diet for a median period of 9.0 months [range 5%-95% (6.0-24.0)]. The anthropometric parameters were measured at baseline and follow-up. All the anthropometric data were converted into standard deviation scores (SDS). A linear regression model was used to investigate the association of lactose intolerance with growth parameters.ResultsWe found no difference in height velocity SDS between the LI and control groups [SDS difference (95% CI): 0.52 (−1.86 to 2.90)]. In addition, we found a significant reduction in the clinical score of the LI group after a lactose-free diet [median (5%-95%): 7.5 (4.0-15.0) and 3 (0.0-8.0); p-value <0.001].ConclusionsThe LI group exhibited no difference in height velocity compared with the control group. Nonetheless, due to the small sample size, the results on the anthropometric profile of the LI group require careful interpretation. More large-scale studies in the pediatric population are required to better understand the association of LI with anthropometric and metabolic profiles.